2016
DOI: 10.1021/jacs.5b12378
|View full text |Cite
|
Sign up to set email alerts
|

Multidentate Polymer Coatings for Compact and Homogeneous Quantum Dots with Efficient Bioconjugation

Abstract: Quantum dots are fluorescent nanoparticles used to detect and image proteins and nucleic acids. Compared with organic dyes and fluorescent proteins, these nanocrystals have enhanced brightness, photostability, and wavelength tunability, but their larger size limits their use. Recently, multidentate polymer coatings have yielded stable quantum dots with small hydrodynamic dimensions (≤10 nm) due to high-affinity, compact wrapping around the nanocrystal. However, this coating technology has not been widely adopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
125
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(134 citation statements)
references
References 72 publications
9
125
0
Order By: Relevance
“…We recently screened a variety of intermediate ligands and found that weakly bound X-type ions (hydroxide) [47] are optimal for yielding compact and homogeneous products (Fig. 8d) due to their high charge that stabilizes the particles in polar solvents and allows rapid displacement by multidentate polymers [189]. By heating at high temperature (110°C), small QD clusters are dissociated, the polymer is densely packed, and QY can be high, generating homogeneously coated nanocrystals with a hydrodynamic size of 7-12 nm with exceptional stable in aqueous solution in ambient conditions for more than one year without noticeable size changes [184, 214].…”
Section: Surface Engineering For Biomedical Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently screened a variety of intermediate ligands and found that weakly bound X-type ions (hydroxide) [47] are optimal for yielding compact and homogeneous products (Fig. 8d) due to their high charge that stabilizes the particles in polar solvents and allows rapid displacement by multidentate polymers [189]. By heating at high temperature (110°C), small QD clusters are dissociated, the polymer is densely packed, and QY can be high, generating homogeneously coated nanocrystals with a hydrodynamic size of 7-12 nm with exceptional stable in aqueous solution in ambient conditions for more than one year without noticeable size changes [184, 214].…”
Section: Surface Engineering For Biomedical Applicationsmentioning
confidence: 99%
“…Norbornene-tetrazine cycloaddition reactions [217, 218] and strain-promoted azide-cyclooctyne cycloaddition reactions [189, 273] have been found to be fully compatible with QDs. These reactions are often quantitative in yield and therefore do not require purification, in contrast to conventional amide-generating coupling for which extensive purification steps are required.…”
Section: Attachment To Molecular Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several designs of these ligands have been tuned to increase bond strength, stability and solution properties of QDs. Similarly the procedure for ligand exchange may additionally influence the polydispersity of the water-solubilized QDs [17,18].…”
Section: Ligand Exchangementioning
confidence: 99%
“…Selvin's lab has developed its own version of quantum dots that are smaller, closer to 9 nm in diameter 7 . That size reduction helps him to slip quantum dots into the approximately 20-40 nm gap between nerve cells, the synapse, where signalling molecules pass on messages to nearby nerve cells.…”
Section: Cracking Open the Cellmentioning
confidence: 99%